Subphthalocyanine basicity: reversible protonation at the azomethine bridge. (27th November 2017) - Bernhard, Yann; Lioret, Vivian; Decréau, Richard A.
Abstract : Protonation of subphthalocyanine azomethine bridges is reversible and was evidenced by UV/Vis, 1 H-NMR and IR. Abstract : Subphthalocyanine (SubPc) could be reversibly protonated at the azomethine bridge. This phenomenon was examined by addressing the p K a of the acid (TFA, MSA, TMSA) and the SubPc electron-withdrawing properties of the peripheral isoindolic substituents (F12 vs. H12 and NO2 ), which tunes the basic character of the azomethine moiety. The protonation of up to three azomethines was suggested and monitored spectrophotometrically with the appearance of new absorption bands at 610, 630 nm and 660 nm, together with marked colour changes from purple to blue to green. Evidence of such a protonation was also shown by significant changes in the 1 H-NMR spectrum and new bands in the infrared spectrum.